Inclusion of the Inducible Caspase 9 Suicide Gene in CAR Construct Increases Safety of CAR.CD19 T Cell Therapy in B-Cell Malignancies - Guercio, Marika; Manni, Simona; Boffa, Iolanda; Caruso, Simona; Di Cecca, Stefano; Sinibaldi, Matilde; Abbaszadeh, Zeinab; Camera, Antonio; Ciccone, Roselia; Polito, Vinicia Assunta; Ferrandino, Francesca; Reddel, Sofia; et al. (Frontiers in Immunology, 2021)
T cells engineered with Chimeric Antigen Receptor (CAR T-cells) are an effective treatment in patients with relapsed/refractory B-cell precursor acute lymphoblastic leukemia or B-cell non-Hodgkin lymphoma. Despite the exciting clinical results, CAR-T cell approach needs efforts to improve the safety profile, limiting the occurrence of adverse events in patients undergoing this treatment. Indeed, beside the most common side effects, such as cytokine release syndrome and CAR-T cell-related encephalopathy syndrome, another potential issue involves the inadvertent transduction of leukemia B cells with CAR construct, during manufacturing process, thus leading to the possibility of a peculiar mechanism of antigen masking and treatment resistance. In this study, we investigated whether the inclusion of the inducible caspase 9 (iC9) suicide gene in the CAR construct design could be an effective safety switch to control malignant CAR+ B-cell, ultimately counteracting this serious adverse event. iC9 is a suicide gene able to be activated through binding with an otherwise inert small bio-molecule, known as AP1903. The exposure of iC9.CAR.CD19-DAUDI lymphoma and iC9.CAR.CD19-NALM-6 leukemia cells in vitro to 20 nM AP1903 resulted into the prompt elimination of CAR+ B-leukaemia/lymphoma cell lines. The results obtained in the animal model corroborate in vitro data, since iC9.CAR.CD19+ tumor cells were controlled in vivo by the activation of the suicide gene through administration of AP1903. Altogether, our data indicate that the inclusion of iC9 suicide gene may results in a safe CAR-T product, even when manufacturing starts from biological materials characterized by heavy leukemia blast contamination.